Two Decades of Smart-Valleys Research: Insights, Knowledge Gaps, and Future Directions for Locally Led Adaptation in Africa Inland Valley Food Systems - Dossou-Yovo, E.R.; Akodekou, A.D.; Futakuchi, K. (2025)
Rice is a staple food for over 750 million people in sub-Saharan Africa (SSA), yet regional self-sufficiency remains below 60%, with the region relying heavily on imports. Inland valleys, covering approximately 190 million hectares, offer significant potential for sustainable rice intensification due to their fertile soils, natural water retention, and favorable microclimates. Beyond agricultural productivity, these landscapes provide critical ecosystem services—including water regulation, biodiversity support, carbon sequestration, and flood mitigation—and sustain multiple stakeholders, from smallholder farmers to pastoralists and fishers. However, uncontrolled expansion and conventional intensification threaten ecosystem integrity and local livelihoods. The Smart-Valleys approach, developed by AfricaRice and partners, provides a locally led, participatory, and nature-based framework for inland valley development. By integrating low-cost water-control infrastructure, community governance, and adaptive management, Smart-Valleys simultaneously enhances productivity, strengthens climate resilience, supports social inclusion, and preserves ecosystem services. Evidence from eleven SSA countries demonstrates substantial gains in rice yields, income, labor efficiency, and ecosystem function, while highlighting the importance of community ownership in scaling. This review synthesizes the methodology, impacts, scaling pathways, and remaining knowledge gaps, emphasizing the role of locally led adaptation and providing research priorities to guide policy and large-scale deployment of Smart-Valleys as a climate-smart, ecosystem-based solution for sustainable rice landscapes in SSA.